A process mining approach to improve emergency rescue processes of fatal gas explosion accidents in Chinese coal mines. (January 2019) - He, Zhen; Wu, Qiong; Wen, Lijie; Fu, Gui
Highlights: The technique of process mining is presented to discover bottlenecks and position deviations of gas explosion accident emergency rescue processes in underground coal mines. The feasibility and advantage of extracting emergency rescue process model for GEAs from historical events log is validated and the emergency rescue process is characterized in the meantime. The average length of cases is 23.72 events, 60% of the cases are below the average length, and 40% of the cases exceed the average length. Considerable GEAs consume more time for emergency rescue compared with major GEAs, emergency rescue of GEAs in north part of China consumes more time compared with south part of China, the accident site of heading face is slightly higher than coal face in emergency rescue time, the emergency rescue duration is least affected by coal mine ownership; compared with case length, the factors of accident grade, coal mine region and accident site possess greater influence on case duration. 56% of the cases take less than two days, 38% of the cases take less than one day, 16% of the cases take less than half a day, while 14% of the cases take more than 10 days. The resources of emergency rescue headquarters, barmaster and medical staff share a better centrality in GEA emergency rescue processes. Abstract: Gas explosion has always been one of the major accident types in the coal mines of China, and reliable emergency rescue process is one of the key guarantees to minimize accident losses. As an emerging discipline to discover bottlenecks and position deviations of processes, process mining is widely used to improve various business processes in recent years. Nevertheless, scarcely does any research apply it to the field of coal mine emergency rescue to our knowledge. In this study, we apply the technique of process mining to domain of gas explosion accident emergency rescue in coal mines. 50 considerable and major gas explosion accidents, which occurred from the second half of 2006–2014 in Chinese coal mines, are selected as log data. The aspects of control-flow perspective, case perspective, helicopter view, organizational dimension and performance perspective are analyzed by process mining. In terms of control-flow perspective, the emergency rescue model is extracted by the inductive miner in ProM, correspondingly, conformance checking and comparison with real-life model have shown the validity of our work. Research also shows that the average length of cases is 23.72 events, and 60% of the cases are under the average length; 56% of the gas explosion accident emergency rescue processes last less than two days; emergency rescue headquarters, barmaster and medical staff share the highest centrality in social network of rescue; the rescue performance is more affected by accident grade, compared with the factors of accident site, region of coal mine and coal mine ownership.